Biosimilars in dermatology - theory becomes reality - Gerdes, Sascha; Enk, Alexander (Journal der Deutschen Dermatologischen Gesellschaft, 2018)
Biosimilars are biological medicines that are analogues of a specific reference product. Biosimilars of the tumor necrosis factor alpha inhibitors infliximab and etanercept are already approved and available for dermatological indications. Regulatory agencies require in-depth analysis of physicochemical and functional properties of these highly complex molecules as well as clinical data on their similarity regarding efficacy and safety in at least one clinical trial in a sensitive and homogeneous population. Thus, it must be shown that biosimilars are essentially the same as the originator product if they are to be licensed in regulated drug markets. As a consequence, these data are extrapolated from one molecule (the originator) to another (biosimilar) resulting in an approval that includes the same indications as the originator product. While extrapolation is well accepted and regulated, clear recommendations regarding the interchangeability of originators and biosimilars as well as data on multiple consecutive switching are missing. Current scientific knowledge does not argue against the use of biosimilars for dermatological indications, but sequential switching of biosimilars should be considered carefully. To increase confidence and enhance evidence for biosimilars, accurate documentation of the specific products given to each patient is essential and should preferably be included in patient registries.
Gesehen am 29.03.2019